Lymphoscintigraphy pre- and post-surgical lymphatic leak repair - Andrews, J T; Binder, L J (Australasian radiology, 1996)
This case report demonstrates the use of lymphoscintigraphy for the localization of a pelvic lymphatic leak. The study was made before and after the operative repair of a lymphatic leak and a marked reduction in the leakage was evident postoperatively. The patient, a 38 year old woman, had a history of adenocarcinoma of the cervix, that was treated by abdominal hysterectomy and pelvic node dissection, and she subsequently developed chylous ascites that required ongoing drainage via a Tenckhoff catheter. This case study illustrates how lymphoscintigraphy aided in the localization of a lymphatic leak and the follow up of surgical repair.